The objective of this research is to formulate a specific model of Citarum’s watershed and its coastal management policy. The method applied in the research is the descriptive method or retrospective through a study case with an approach system. The multidimensional systematic approach is applied to formulate policies, to develop scenario strategies involving several stakeholders and experts on coastal areas and regional and inter sectors. The results of the research determine that the econom - Edwarsyah .; Tridoyo Kusumastanto; Hartrisari Hardjomidjojo; Ario Damar (Forum Pasca Sarjana, 2009)
The objective of this research is to formulate a specific model of Citarum’s watershed and its coastal management policy.  The method applied in the research is the descriptive method or retrospective through a study case with an approach system.  The multidimensional systematic approach is applied to formulate policies, to develop scenario strategies involving several stakeholders and experts on coastal areas and regional and inter sectors.  The results of the research determine that the economical value relating with the aspects of pollution which in general involves replacement costs indicate impacts of pollution from public activities in the coastal stream in de facto costs Rp 31 billion/year.  The Index Value of a Sustainable Watershed and Coastal Management System (IkB-SIPPDAS) applied in the study area according to a multidimensional Rap-SIPPDAS method for upland, center and downstream area of the Citarum’s Watershed are 38.23; 38.27; and 33.59 respectively in a sustainability scale of     0-100, showing a non-sustainable status.  The analysis result for every dimension of development management indicates that the economical dimension for the upland, middle and coastal part of the Citarum Watershed contains the highest index rate, which amounts up to 88.29.  The index value is categorized ”good” or sustainable with the lowest value in ecology.  The results of the statistics indicates that the Rap-SIPPDAS method is effective enough for application as a method to evaluate the Watershed and Coastal Management System in a specific river stream or a rapid appraisal area.  The selected ideal design of the three scenarios for the watershed management policy and West Java’s Citarum coastal area is the progressive-optimistic scenario stressing the possible future condition to receive maximum support or in other words the scenario is based on the scientific way of thinking and being optimistic about the future.   Key words: watershed, coastal, scenario, system, management, pollutant, policy